Participatory Democracy in Action: Survey Evidence from South India - Tim Besley Rohini Pande Vijayendra Rao
We use household and village survey data from South India to examine who participates in village meetings called by elected local governments, and what erect these meetings have on bene_ciary selection for welfare programs. Our main _nding is that it is the more disadvantaged social groups who attend village meetings and that holding such meetings improves the targeting of resources towards the neediest groups.